Working in the "global village": The influence of cultural intelligence on the intention to work abroad - Stefan Remhof; Marjaana Gunkel; Christopher Schlägel (Zeitschrift für Personalforschung (ZfP), 2013)
Firms' international activities require an early identification of potential employees with an intention to work abroad. Based on social cognitive theory the current study examines the influence of prior international exposure and cultural intelligence on the individual intention to work abroad. In particular, we examine the influence of language skills, international experience, and networks abroad on the intention to work abroad through cultural intelligence and the moderating role of cultural distance on this mediated relationship. Utilizing a sample of 518 German business students we show that networks abroad have a direct influence on the intention to work abroad, while cultural intelligence fully mediates the relationship between language skills as well as international experience and the intention to work abroad. Cultural distance moderates this mediation for two of the four cultural intelligence dimensions. – – Die internationalen Aktivitäten von Unternehmen erfordern eine frühe Identifikation von Mitarbeitern für potentielle Auslandseinsätze. Basierend auf der sozialkognitiven Theorie untersuchen wir den Effekt des vorherigen internationalen Einflusses sowie der kulturellen Intelligenz auf die individuelle Intention, eine Position im Ausland anzunehmen. Insbesondere betrachten wir den Einfluss von Fremdsprachenkenntnissen, vorheriger Auslandserfahrung und des bestehenden Auslandsnetzwerkes auf die Intention, im Ausland zu arbeiten und die moderierende Funktion der kulturellen Distanz auf die mediierende Wirkung der kulturellen Intelligenz auf diese Beziehung. Auf der Grundlage einer Stichprobe von 518 deutschen Studenten der Wirtschaftswissenschaften zeigen die Ergebnisse, dass das Auslandsnetzwerk einen direkten Einfluss mediiert, während kulturelle Intelligenz den Effekt von Fremdsprachenkenntnissen und internationaler Erfahrung auf die Absicht, im Ausland zu arbeiten, mediiert. Die kulturelle Distanz moderiert diese Mediation für zwei der vier Dimensionen der kulturellen Intelligenz.
Keywords: F22; F23; F60; J61; M51; 650; international exposure; cultural intelligence; cultural distance; intention to work abroad; self expatriation